Pengaruh Pendapatan Asli Daerah dan Dana Alokasi Khusus terhadap Belanja Modal - Nida Rizqia Fikra (BUDGETING : Journal of Business, Management and Accounting, 2022)
This study aims to determine how the influence of Regional Original Income (PAD) and Special Allocation Funds (DAK) on the Sukabumi Regency Government Capital Expenditure. The research method used in this study is associative and descriptive methods. The data collection technique in this research is secondary data, the method used is documentation. The sample in this study is the Budget Realization Report (LRA) of the Sukabumi Regency Government for the 2018-2020 period using 36 data samples, and using the multiple linear regression analysis method. The results showed that the known value of R Square was 0.920 or 92% which indicated that there was a simultaneous influence between the variables of local revenue and special allocation funds on capital expenditures of 92% and the remaining 8% was influenced by other factors not examined. In conclusion, the Regional Original Revenue partially shows that the Regional Original Income (PAD) has a positive and significant effect on Capital Expenditures. Meanwhile, the Special Allocation Fund partially shows that the Special Allocation Fund has no significant effect on capital expenditure. Simultaneously Local Original Revenue and Special Allocation Funds have a positive and significant effect on Regional Capital Expenditures. Keywords: Special Allocation, Capital Expenditure, Regional Original Income